1999
DOI: 10.1136/jcp.52.10.735
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor mRNA expression in minimal change, membranous, and diabetic nephropathy demonstrated by non-isotopic in situ hybridisation

Abstract: Aim-To investigate vascular endothelial growth factor (VEGF) mRNA expression in glomerular disease in the context of heavy proteinuria. Methods-Non-radioisotopic in situ hybridisation was performed using a cocktail of 12 deoxyoligonucleotides complementary to VEGF mRNA labelled during solid phase synthesis with 2,4-dinitrophenyl. Archival renal biopsies were studied from cases of minimal change nephropathy, membranous nephropathy, diabetic nephropathy, and controls, matched for age, sex, race, and storage time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 12 publications
3
65
0
Order By: Relevance
“…NO functions in vasodilation, regulation of smooth muscle proliferation, and expression of cellular adhesion molecules such as VCAM-1. Kidney biopsies from diabetic patients demonstrated reduced levels of VEGF (1). Our studies also demonstrated decreased VEGF levels but increased levels of eNOS and NO, suggesting uncoupling of VEGF-mediated NO production.…”
Section: Discussionsupporting
confidence: 56%
“…NO functions in vasodilation, regulation of smooth muscle proliferation, and expression of cellular adhesion molecules such as VCAM-1. Kidney biopsies from diabetic patients demonstrated reduced levels of VEGF (1). Our studies also demonstrated decreased VEGF levels but increased levels of eNOS and NO, suggesting uncoupling of VEGF-mediated NO production.…”
Section: Discussionsupporting
confidence: 56%
“…Hyperglycemia, the main initiating factor for the microvascular abnormalities, mediates many of its diverse effects by altering the expression of cytokines such as in the increased expression of ET-1 and VEGF (6,7,27). We and others have also reported that the expression and the actions of ET-1 and VEGF are increased not only in the retina but also in the renal glomeruli of diabetic animals (6,28,29). In the present study, we have focused the studies on the expression of ET-1 and PDGF in the pericytes and retina of diabetic animals because both of those cytokines are known to have important effects on pericyte activation, survival, and growth (30 -32).…”
Section: Discussionmentioning
confidence: 84%
“…Enhanced VEGF expression was also observed in retinal pigment epithelial cells stimulated by hypoxia and by advanced glycation products and in osteoblasts that are thought to promote bone formation (35)(36)(37). Renal glomerular expression of VEGF has also been demonstrated, for instance, in glomerular visceral epithelial cells where VEGF may have a role in the induction of proteinuria in renal diseases (38). Both VEGF and VEGF receptors were up-regulated in kidneys of diabetic rats, and administration of monoclonal anti-VEGF antibodies improved early renal dysfunction, as assessed by decreased hyperfiltration, albuminuria, and glomerular hypertrophy, in experimental diabetes, suggesting a role in the pathogenesis of diabetic nephropathy (39,40).…”
Section: Fig 7 Effects Of Sb203580 On Tgf-␤1-stimulated Protein Synmentioning
confidence: 83%